Costa Rican fungi as potential biomaterials - Fallas-Méndez, Adriana (2024)
Fungal biomaterials are gaining relevance due to their intrinsic ability of self-repair, higher sensitivity to external conditions and faster growth respective to synthetic materials. This project consists of evaluating and characterizing the physical properties of fungal strains isolated from a Pacific Coast Mangrove in Costa Rica. We identified environmental strains by recording their morphological features and complemented this by ITS-based DNA barcoding, and subsequently, classified three strains based on morphological features and seven strains by molecular analyses. Ongoing work is being done to measure electrical responses of these fungi upon light stimulation; in addition, a protocol for studying their piezoelectric properties is being developed to identify potential candidates to be used in the field of electronics. To the extent of our knowledge, our project is the first one to report piezoelectric properties from microscopic fungi in Costa Rica as means to determine its potential as biomaterials.